L-ANTITRYPSIN DEFICIENCY. THE ALGORITHM OF ACTIONS IN MAKING A DIAGNOSIS AND DETERMINING THE TACTICS OF PATIENT MANAGEMENT - Ганюкова, Надежда Григорьевна; Гофман, Людмила Сергеевна; Якушенко, Марина Геннадьевна; Елгина, Светлана Ивановна; Рудаева, Елена Владимировна; Мозес, Кира Борисовна (Medicine in Kuzbass, 2025)
The article presents a clinical lecture on alpha-1-antitrypsin (A1AT) deficiency, a genetically determined disease caused by A1AT deficiency in blood serum and manifested in the form of chronic obstructive pulmonary disease, emphysema, liver and vascular damage. Its pathophysiology, diagnosis, treatment and prevention.
Keywords: alpha-1-antitrypsin; etiology; pathogenesis; diagnosis; treatment